Shelf life prediction and Bacterial flora for the fresh and lightly salted Pseudosciaena crocea stored at different temperatures - Lumin, Guo Quanyou; Baoguo, Li; Chaojun, Jiang (Emirates Journal of Food and Agriculture, 2017)
The active dominant spoilage organisms in the farmed Pseudosciaena crocea would cause short shelf life. This study focused on an identification of spoilage bacteria and the development of predictive model of shelf life in Pseudosciaena crocea both fresh and lightly salted during the storage at low, ambient and fluctuating temperature conditions. Microbiological, chemical changes in Pseudosciaena crocea were assessed to ensure the shelf life; Phenotypic and 16S rRNA were used to identified dominated strains from different conditions. Shelf life, remaining shelf life were predicted by predictive models including exponential, school-field and Square-root equation. The results showed that Shewanella spp. was the dominant organism at low temperature, while Vibrio spp. and Enterobacter were the dominant organisms at ambient and fluctuating temperatures.While the Proteus vulgaris, Vibrio alginolytica and serratia were the dominant group at low, ambient and fluctuating environment of the lightly salted Pseudosciaena crocea .The shelf-life of fresh Pseudosciaena crocea were 5.4 ~ 17.8 days, 1.1days and 4.6~9.3 days under low, ambient and fluctuating temperature; while the shelf life of lightly salted Pseudosciaena crocea were 12.2~49.1days, 4.2day and 20.5~23.5 days under low, ambient and fluctuating temperature. The evaluation index showed that School-field model and Exponential model in fresh fish were better, Exponential model was better to predict the shelf life in lightly salted fish. The results can facilitated the establishment of spoilage bacterial Hazard Analysis Critical Control Point during the processing of the Pseudosciaena crocea products.